Modeling and simulation in ecotoxicology with applications in MATLAB and Simulink - Dixon, Kenneth R. (Boca Raton : CRC Press, 2012)
'This book fills the need for quantitative modeling in the field of ecotoxicology recognized for decades. It discusses the role of modeling and simulation in environmental toxicology, and describes toxicological processes from the level of the individual organism to populations and ecosystems. Mathematical functions and simulations are presented using Matlab and Simulink programming languages. Chapters cover principles and practices in simulation modeling; stochastic modeling; modeling ecotoxicology; parameter estimation; model validation; as well as designing and analyzing simulation experiments'--Provided by publisher.
Book is accompanied by 1 CD entitled'Modeling and simulation in ecotoxicology with applications in MATLAB and Simulink' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references and index.
Keywords: Environmental toxicology -- Data processing